PEMBUDIDAYAAN DAN PRODUK OLAHAN JAMUR TIRAM KELOMPOK WANITA TANI BAROKAH MANDIRI - Eka Siswanto; Supomo Supomo; Ameliora Dwi Astani; Otong Asnawi; Wiranto Wiranto; Nur Annisa Aisywarya (Jurnal Abdi Masyarakat Kita, 2026)
Oyster mushroom processed products as healthy food and consumed by the community cultivated from the harvest of the Barokah Mandiri Women Farmers Group through a group of housewives in the Muara Jawa Tengah sub-district, Kutai Kartanegara district. The problem of the partner, namely the Barokah Mandiri Women Farmers Group, is the lack of knowledge and information from the community about Oyster Mushroom processing with various variants that are not widely known in terms of how and what form of oyster mushroom processed products such as mushroom chips, mushroom floss, and mushroom nuggets. The purpose community service from Sekolah Tinggi Ilmu Kesehatan Samarinda (STIKSAM) is to provide added value to the Oyster Mushroom as a home business opportunity because it has a fairly high nutritional content that can be processed into various delicious foods. The methods used are (1) training/training in oyster mushroom cultivation; (2) Continuous education; (3) awareness; (4) digital marketing. The results obtained from the implementation of this community service are emphasized program outputs that can be in the form of processed mushroom food products (chips, floss and nuggets) produced by partners as an indicator of the success of the program.